Observatorio y desarrollo sostenible - López López, Alejandro (Observatorio Medioambiental, 2007)
A growing concern for the environment, intensified in recent decades, has led to the need to re-examine old fashioned ideas about a limitless world with natural resources so abundant they can be used and abused at pleasure. The traditional concept of economic growth and developmente has begunto evolve toward one envisioning a balance between society and the environment, giving rise to the idea of sustainable growth.